Enhancing Disaster Resilience: Leveraging Raspberry Pi Technology for Natural Disaster Management Information Systems - Harukap, Kayo; Shizuka, Takara (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2024)
Natural disasters pose significant threats to human lives, infrastructure, and ecosystems, necessitating effective disaster management strategies to mitigate their impacts. In this research, we explore the design and implementation of a Natural Disaster Management Information System (NDMIS) using Raspberry Pi technology. The NDMIS leverages Raspberry Pi's versatility, affordability, and scalability to collect, process, and analyze real-time data, enabling stakeholders to make informed decisions and take proactive measures during disaster events. Through interdisciplinary collaboration and community engagement, the research demonstrates the transformative potential of Raspberry Pi in democratizing access to critical information and resources, empowering communities to build resilience and enhance disaster response capabilities. The findings underscore the importance of technological innovation, community empowerment, and interdisciplinary collaboration in advancing disaster management practices. Furthermore, the research identifies future research directions, including algorithm optimization, interoperability, and human-centered design, aimed at further enhancing the effectiveness and scalability of NDMIS solutions. This research represents a significant step towards leveraging Raspberry Pi technology for building more resilient, adaptive, and sustainable communities in the face of natural disasters.